2011
DOI: 10.5897/ajpp11.024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitamin B6 on age associated changes of rat brain glutamate decarboxylase activity

Abstract: Glutamate and gamma-aminobutyric acid (GABA), act as excitatory and inhibitory neurotransmitters in CNS respectively. An increase in glutamate and a decrease in GABA concentration were observed in aged brain. However, the mechanism of these changes has not been very well elucidated. Glutamate decarboxylase (GAD) catalyzes the conversion of glutamate to GABA. Since the vitamin B6 is essential for the activities of GAD, this study was undertaken to investigate the effects of vitamin B6 administration on age rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Therefore plausibly single dose of MSG did not have depressogenic effects in adult mice because of the matured BBB. In addition age associated changes in brain neurotransmitters' metabolism are thought to be important and could possibly lead to many age-related symptoms [20]. Vitamin B6 had beneficial antidepressant effects in both age groups.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore plausibly single dose of MSG did not have depressogenic effects in adult mice because of the matured BBB. In addition age associated changes in brain neurotransmitters' metabolism are thought to be important and could possibly lead to many age-related symptoms [20]. Vitamin B6 had beneficial antidepressant effects in both age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Previously results showed that GAD activity is considerably reduced in the brain of old rats compared to the young animals [20]. That could influence the glutamate and GABA level concentration in favor of glutamate accumulations in certain brain regions [20].…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Age related decreases in the expression and or activities of these enzymes in the brain have been very well established (9,10). Recently we have reported that the activity of GAD in aged rats brain was 54% lower than that of young animals, which could be reactivated to the levels equivalent to young animals by administration of vitamin B6 [11]. Because pyridoxal 5'-phosphate acts as co-enzyme for aminotransferases as well, this study was extended to examine the effects of vitamin B6 administration on the brain glutamate pyrovate transaminase (GPT) and glutamate oxaloacetate transaminase (GOT)) in young and old rats.…”
Section: Introductionmentioning
confidence: 93%